Percutaneously Inject able Fetal Pacemaker: Electrodes, Mechanical Design and Implantation - Zhou, Li (Conf Proc IEEE Eng Med Biol Soc, 2012)
We are developing a self-contained cardiac pacemaker with a small, cylindrical shape (~3×20mm) that permits it to be implanted percutaneously into a fetus to treat complete heart block and consequent hydrops fetalis, which is otherwise fatal. The device uses off-the-shelf components including a rechargeable lithium cell and a highly efficient relaxation oscillator encapsulated in epoxy and glass. A corkscrew electrode made from activated iridium can be screwed into the myocardium, followed by release of the pacemaker and a short, flexible lead entirely within the chest of the fetus to avoid dislodgement from fetal movement. The feasibility of implanting the device percutaneously under ultrasonic imaging guidance was demonstrated in acute adult rabbit experiments.